Fulfillment Of Women's Educational Rights According To Universal Declaration Of Human Right (UDHAM) And Islamic Law - Astuti, Mirsa; Nadirah, Ida; Aksa, Muhammad Faris (DE LEGA LATA: JURNAL ILMU HUKUM, 2023)
This research is to see the fulfillment of women's educational rights according to the Universal Declaration of Human Rights (UDHR) and Islamic law. The problem is what is the right to education for women according to the UDHR and how Islamic law views women's right to education. The method used to achieve the objectives of this research is normative legal research, namely research whose data is sourced from secondary data. The nature of this research is descriptive, which aims to provide an overview of women's rights to education. The research results show that education is the key to freedom which helps an individual to develop himself and then contribute to society. This concept has become an international consensus. In the context of human rights, education is a human right that must be respected, fulfilled and protected. In the UDHR it is known that every individual has the right to obtain education, at least basic education. When some people find it difficult to obtain the right to education which is their basic right, the party who is obliged to fulfill this right is none other than the state. Islam places women in a very noble position. Islam does not prohibit women from studying and teaching knowledge, in fact it is Islam that requires them to seek knowledge and gives them the freedom to provide teaching about the knowledge they have mastered. Islam does not deny the intelligence of women.